Cardinal Fish Otolith Biometrics Banggai Pterapogon kauderni Koumans, 1933 In the Front Waters of Dudepo TPI Dudepo, South Bolaang Mongondow Regency and in the Lembeh Strait, Bitung City - Melani, Hellen; Rondonuwu, Ari B.; Sangari, Joudy R.R; Manginsela, Fransine B.; Pratasik, Silvester B.; Undap, Suzanne L. (Jurnal Ilmiah Platax, 2023)
This study aims to determine the biometric comparison of otoliths of Banggai cardinal fish based on gender and to determine the comparison of otolith biometrics at two locations in the Waters Front of TPI Dudepo Kab. South Bolaang Mongondow and in the Lembeh Strait, Bitung City. Data collection in the field using the roaming survey method. Fishing is done by snorkelling, catching a minimum of 50 individuals representing each size class using Chang net/Sibu fishing gear. The differences in otoliths in male and female sexes have seven different otolith characters in otolith length (OL), otolith width (OW), otolith area (OA) and otolith perimeter (OP), roundness (Rnd), ellipticity (Ell) and aspect ratio (Ar), and three characters that do not show significant differences, namely form factor (Ff), circularity (Cir), rectangularity (Rec). The differences in otoliths based on location in front of the Dudepo TPI and in the Lembeh Strait have seven different otolith characters in otolith length (OL), otolith width (OW), otolith area (OA) and otolith perimeter (OP), roundness (Rnd), ellipticity (Ell). and aspect ratio (Ar), and three characters that do not show significant differences, namely form factor (Ff), circularity (Cir), rectangularity (Rec). Keywords: Biometrics, cardinal proud fish, comparison Abstrak Penelitian ini bertujuan untuk mengetahui perbandingkan biometrik otolit ikan kardinal banggai berdasarkan jenis kelamin dan mengetahui perbandingan biometrik otolit pada dua lokasi di Perairan Depan TPI Dudepo Kab. Bolaang Mongondow Selatan dan di Selat Lembeh Kota Bitung. Pengambilan data di lapangan menggunakan metode survei jelajah. Penangkapan ikan dilakukan dengan penyelaman snorkling, penangkapan minimal 50 individu yang mewakili setiap kelas ukuran dengan alat tangkap Chang net/Sibu. Perbedaan otolit pada jenis kelamin jantan dan jenis kelamin betina memiliki tujuh perbedaan karakter otolit pada panjang otolit (OL), lebar otolit (OW), area otolit (OA) dan perimeter otolit (OP), roundness (Rnd), ellipticity (Ell) dan aspect ratio (Ar), dan tiga karakter yang tidak menunjukkan perbedaan yang signifikan, yaitu form factor (Ff), circularity (Cir), rectangularity (Rec). Perbedaan otolit berdasarkan lokasi di depan TPI Dudepo dan di Selat Lembeh memiliki tujuh perbedaan karakter otolit pada panjang otolit (OL), lebar otolit (OW), area otolit (OA) dan perimeter otolit (OP), roundness (Rnd), ellipticity (Ell) dan aspect ratio (Ar), dan tiga karakter yang tidak menunjukkan perbedaan yang signifikan, yaitu form factor (Ff), circularity (Cir), rectangularity (Rec). Kata kunci: Biometrik, ikan banggai kardinal, perbandingan